Credit Institutions in the Republic of Croatia in the Period From 1991 to 2020. - Filipović, Mario; Peronja, Ivan; Karin, Ivan (Transactions on Maritime Science, 2022)
It can be said that there is a day in the entire world when a company is not established or ceases its activity. Among these companies, credit institutions also have their place. The requirements that must be met when establishing banks and other credit institutions are as a rule, more rigorous than when establishing other business entities. Therefore, credit institutions are established less frequently. It can also be noted that they disappear from economic life less frequently. The emergence, and especially the disappearance of a credit institution does not go unnoticed. The same is true for other companies, unless they belong to a group of large and globally known companies. The aim of this paper is to analyse the trends in the establishment and failure of credit institutions in the Republic of Croatia in the period from 1991 to 2020. The research was conducted by studying domestic and foreign scientific and other relevant literature.